Privacidade do usuário na atividade de busca: O caso do Arquivo Público do Estado de São Paulo - Gonçalez, Paula Regina Ventura Amorim [UNESP]; Santana, Ricardo César Gonçalves [UNESP]; Jorente, Maria José Vicentini [UNESP] (FapUNIFESP (SciELO), 2015)
With the advent of the Internet, it has become possible to overcome timelines with a gain in knowledge by identifying that information available were seldomly accessed by a number of potentially expanded users through the use of Information and Communication Technologies. From the year 2003, before these new possibilities, the Public Archives of the State of São Paulo magnified the way it operates to provide part of its collection of documents on the Web environment, disseminating archival information and making them accessible. The popularization of the Internet and the public policies that guarantee access to information for all citizens through the Access to Information Act. Guided this study, aimed towards the application of Framework for privacy analysis, presented by Rubel and Biava (2014) on access to information in the environments of Public Archives of the state of São Paulo. The methodology consisted of a theoretical investigation based on the principles of privacy in the physical, exploratory and digital environment, and from the visit and observation of said file in its physical and digital environments. As a result, it was found that the use of framework allows understanding of varying complexity problems in the degree of privacy of users in different environments.
User privacy in search activity: The case of the public archives of the state of são paulo
Keywords: Information technology; Permanent archives; Privacy; Web